Harriet Tubman - Sullivan, George, 1927- (New York : Scholastic Reference, 2002)
Using a variety of primary sources, this biography of Harriet Tubman describes the life of a former slave who was responsible for helping many other slaves to freedom.
2 Not Worth a Sixpence 10 -- 3 Brush with Death 19 -- 4 Hired Out 26 -- 5 John Tubman 32 -- 6 Escape 37 -- 7 First Passengers 45 -- 8 The Trackless Trail 52 -- 9 A Woman Called Moses 60 -- 10 General Tubman 70 -- 11 Rescue in Troy 79 -- 12 Nurse, Scout, Spy 86 -- 13 Return Home 97 -- 14 Final Years 102.
Includes bibliographical references (p. 120-121) and index.
Middle School.
660
Accelerated Reader
Reading Counts!
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Slaves -- United States -- Biography -- Juvenile literature; African American women -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground Railroad -- Juvenile literature